Keynes, the Keynesians and the exchange rate (2007)
One of the most quoted remarks in economics comes in the final chapter of Keynes’s General Theory of Employment, Interest and Money, where he says: the ideas of economists, both when they are right and when they are wrong, are more powerful than is commonly understood. Indeed the world is ruled by little else. Practical men, who believe themselves to be quite exempt from any intellectual influences, are usually the slaves of some defunct economist. Madmen in authority, who hear voices in the air, are distilling their frenzy from some academic scribbler of a few years back